Survei Awal Studi Perbandingan Al-Qur’an dan Bibel dalam Kesarjanaan Barat: - Lien Iffah Naf'atu Fina (Lajnah Pentashihan Mushaf Al-Qur'an, 2015)
The Qur'an and the Bible have some similarities. These similarities have invited many scholars to conduct comparative studies on these two scriptures. This paper focuses on the comparative study of the history of these two scriptures among the Western scholars. It is through this article, the very signifcant shifting in the outlook of Western scholars on the relationship of the Koran and the Bible will be seen clearly, from a negative perspective of the Koran to a positive appreciation one. The shifting was made possible by the birth of inter-textuality discipline in social and humanity studies which look that every text is unique and thus cannot be compared (incommensurable).